Democracy In Türkiye and Indonesia - Soydan, Mustafa Zafer; Setiawan, Refly (LPPM Universitas Lampung, 2023)
Currently, democracy has given its place to people all over the world, both in Türkiye and Indonesia. In various countries, especially in Türkiye and Indonesia, the government is always faced with various problems, especially related to democracy. One of the problems of democracy in Türkiye is related to the social structure. In Turkish society, where traditional social characteristics are dominant, individual life is not a pleasant lifestyle and social characteristics do not allow it. Although the ongoing modernization efforts throughout the history of the Republic of Türkiye have united the society with modern life to some extent, when viewed as a whole, it is seen that the society still develops attitudes and behaviors suitable for the characteristics of Turkish culture. In addition, Indonesian society also has its own characteristics, and the way in which Indonesia implements democracy also refers to the situation of a multi-ethnic country, so every policy made by the government takes great care not to cause political turmoil in the society. In this study, the researcher places more emphasis on the theories and concepts of democracy related to Türkiye and Indonesia. Several theories related to democracy are used to support this research in order to provide a clear picture of democracy in Türkiye and Indonesia.